Strategi Guru Dalam Mengatasi Kendala Penggunaan Media Pembelajaran PAI Pada Masa Pandemi Covid-19 - Deli, Yasni; Sulaiman, Sulaiman (An-Nuha, 2023)
This study aims to disclose information and discuss teacher strategies in overcoming obstacles to the use of PAI learning media during the Covid-19 pandemic at SMA N 1 Harau. This type of research is descriptive research with a phenomenological approach. Data collection comes from interviews and observations, as well as documentation. Interviews were conducted with five informants, consisting of two pie subject teachers and two class IX students and another informant from class XII. The research was conducted from June to July. This research consists of two cycles, namely the planning and implementation stages. To obtain research data, four data collection tools were used, namely field notes, tests, observation and documentation. In the planning stage, the PAI teacher prepares a list of questions according to the research for the resource persons. Furthermore, at the implementation stage, the researcher processes data related to the research. In order to obtain information on the strategies and efforts of teachers in overcoming obstacles to the use of learning media.